2016
DOI: 10.1186/s40064-016-1699-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect and clinical significance of fast-track surgery combined with laparoscopic radical gastrectomy on the plasma level of vascular endothelial growth factor in gastric antrum cancer

Abstract: This study discusses the effect and clinical significance of fast-track surgery (FTS) combined with laparoscopic radical surgery on the plasma level of vascular endothelial growth factor (VEGF) in locally advanced gastric antrum cancer. Plasma VEGF levels were detected in 63 cases of locally advanced gastric antrum cancer by using double-antibody sandwich Avidinbiotincomplex-ELISA before and after operation. The pure laparoscopic surgery group (group A) comprised 30 cases, and the combined FTS group (group B) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The outcome variables (postoperative hospital stay, duration to first flatus after surgery, hospitalization expenditure, and short-term complication) extracted from these studies are presented in Table 2 . Two studies did not report duration to first flatus after surgery, and three studies did not report hospital charge [ 15 , 17 , 18 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome variables (postoperative hospital stay, duration to first flatus after surgery, hospitalization expenditure, and short-term complication) extracted from these studies are presented in Table 2 . Two studies did not report duration to first flatus after surgery, and three studies did not report hospital charge [ 15 , 17 , 18 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Only three studies reported duration to first flatus after surgery [ 14 , 16 , 17 ]. There was significant heterogeneity among the studies ( I 2 = 90%, P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Elements of the ERAS pathways for different surgical subgroups are essentially the same with minor modifications. [1516171819202122232425262728293031323334353637383940414243444546474849] General elements include preoperative nutritional screening, no preoperative bowel preparation, maltodextrin drink 2 h before surgery, prophylactic antibiotics, epidural or patient-controlled analgesia, prokinetic agents, goal-directed fluid therapy, early mobilisation, predefined criteria for removal of drains, nasogastric tubes and catheters, immediate extubation, early oral intake and a specific discharge plan. Surgery-specific elements like octreotide for pancreaticoduodenectomies, minimal tissue handling and minimally invasive surgery for urogynaecological oncosurgery or pharmacological thromboprophylaxis for head and neck free-flap surgery are important.…”
Section: Eras Pathwaymentioning
confidence: 99%
“…Given the strong evidence and recommendations for colorectal cancer, the application of ERAS protocols for gastrectomy procedures has been investigated in several studies[ 16 - 19 ]. ERAS principles combined with laparoscopic treatment for GC lead to satisfactory clinical outcomes[ 20 - 22 ], even in elderly patients[ 23 , 24 ]. Several meta-analyses have revealed that ERAS pathways in GC patients reduce the duration of hospital stay and medical costs without significantly increasing complications and hospital readmission[ 25 - 28 ], and the ERAS Society issued consensus guidelines for perioperative care after elective gastrectomy for GC in 2014[ 29 ].…”
Section: Introductionmentioning
confidence: 99%